Evolution and Research Trends of QRIS: A Bibliometric Analysis on the Implementation of Digital Payment Standard in Indonesia - Suginam, Suginam (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
The Quick Response Code Indonesian Standard (QRIS) has emerged as a key initiative in advancing the digitalization of payment systems in Indonesia. However, literature on its implementation, challenges, and impact on the digital payment ecosystem remains scattered and insufficiently structured. This study aims to identify trends, patterns, and research directions related to QRIS through a bibliometric analysis. Bibliographic data were collected from leading databases such as Scopus, covering relevant publications up to 2024. The analytical approach includes bibliometric techniques such as co-occurrence analysis, co-authorship analysis, and visualization using tools like Bibliometrix and Biblioshiny. The study reveals that QRIS adoption focuses on financial inclusion, payment efficiency, and technological adaptation in the MSME sector. Additionally, significant research trends highlight institutional collaboration and contributions from researchers in developing countries. The findings indicate that QRIS holds substantial potential to drive digital transformation; however, challenges such as technological infrastructure, digital literacy, and regulatory frameworks remain major barriers. This study provides strategic insights for policymakers, academics, and industry players to strengthen QRIS implementation comprehensively. Consequently, it is expected to serve as a foundation for further research exploring the role of QRIS in building an inclusive and sustainable financial ecosystem.